2014
DOI: 10.1155/2014/740947
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Th17, Th22, and Th1 Cells Are Elevated in the Guillain-Barré Syndrome and Downregulated by IVIg Treatments

Abstract: The Guillain-Barré syndrome (GBS) is considered a T helper 1 (Th1) cells-mediated acute inflammatory peripheral neuropathy. However, some changes in GBS could not be explained completely by Th1 cells pathogenic role. Recently, Th17 cells have been identified and can mediate tissue inflammation and autoimmune response. Therefore, a study on the role of Th17 and Th22 cells and their cytokines in GBS is necessary for exploring the pathogenesis of GBS. Here, we detected the frequency of Th1, Th17, and Th22 cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 42 publications
2
40
0
1
Order By: Relevance
“…jejuni induces the unbalance of Th1/Th2/Th17/Treg and cytokines that is crucial for the development of GBS [14]. In addition, Th17 also plays a pathogenic role, and elevated circulating Th22 cells are correlated with severity of disease, but not with GBS subphenotypes [48]. In addition, Th17 also plays a pathogenic role, and elevated circulating Th22 cells are correlated with severity of disease, but not with GBS subphenotypes [48].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…jejuni induces the unbalance of Th1/Th2/Th17/Treg and cytokines that is crucial for the development of GBS [14]. In addition, Th17 also plays a pathogenic role, and elevated circulating Th22 cells are correlated with severity of disease, but not with GBS subphenotypes [48]. In addition, Th17 also plays a pathogenic role, and elevated circulating Th22 cells are correlated with severity of disease, but not with GBS subphenotypes [48].…”
Section: Pathogenesismentioning
confidence: 99%
“…Up regulation of Th1 cytokines in the early disease course may be associated with immune-mediated disease progression due to neuronal inflammation, but up regulation of Th2 immune response during the later phase aids recovery from the disease [47]. Th17 and Th22 cells of GBS patients at acute phase could express an appropriate cytokine profile, like IL-17, IL-22, and others (IL-6 and TNF-), which can enhance the inflammatory and autoimmune response and conduce to the development of GBS [48]. Th17 and Th22 cells of GBS patients at acute phase could express an appropriate cytokine profile, like IL-17, IL-22, and others (IL-6 and TNF-), which can enhance the inflammatory and autoimmune response and conduce to the development of GBS [48].…”
Section: Pathogenesismentioning
confidence: 99%
“…Although no studies have identified specific T cell epitopes involved, it is clear that their formation is T cell-dependent. Several populations of T-helper cells have been identified in cases of C. Jejuni-induced GBS [78], and immunoglobulin class-switching has been observed in transgenic mice that lack complex ganglioside when immunized with C. Jejuni LPS [79]. Evaluation of potential cross-reactivity between GBS-associated antigens in pathogens and self is both feasible and actionable using JanusMatrix.…”
Section:  Guillain-barré Syndromementioning
confidence: 99%
“…36 Applications of JanusMatrix may be relevant, therefore, in the context of autoimmune diseases following vaccination, such as Guillain-Barre syndrome or Narcolepsy. [37][38][39] Finally, pathogen subterfuge may teach us something about our own immune system. What is the role of human peptide epitopes that are themselves cross-reactive with other human sequences?…”
Section: Resultsmentioning
confidence: 99%